2018
DOI: 10.3168/jds.2017-14329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ensiling time on fermentation profile and ruminal in vitro starch digestibility in rehydrated corn with or without varied concentrations of wet brewers grains

Abstract: The objective of this study was to evaluate the effect of rehydrating and ensiling dry ground corn (DGC) with varying concentrations of wet brewers grain (WBG) on fermentation profile and ruminal in vitro starch digestibility (ivSD; 7-h incubations on dried and 4-mm ground samples). Samples of DGC and WBG were weighed separately and mixed into 100% WBG (WBG); mixture of DGC and WBG targeting 60 (RC60), 65 (RC65), or 70% (RC70) of dry matter (DM); and DGC rehydrated with distilled water targeting for 70% of DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
(41 reference statements)
6
14
0
2
Order By: Relevance
“…In experiments with reconstitution of dry sorghum grain at three moisture levels, Huck et al (1999) found pH values of 5.0, 4.4 and 4.05 for the DM contents of 75, 60 and 55%, respectively, which are very similar to those of the present study. However, Ferraretto et al (2018) found a slightly lower pH for silages of corn grain reconstituted with 30% moisture. The obtained pH data was 4.0 for silage with 28 days fermentation.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In experiments with reconstitution of dry sorghum grain at three moisture levels, Huck et al (1999) found pH values of 5.0, 4.4 and 4.05 for the DM contents of 75, 60 and 55%, respectively, which are very similar to those of the present study. However, Ferraretto et al (2018) found a slightly lower pH for silages of corn grain reconstituted with 30% moisture. The obtained pH data was 4.0 for silage with 28 days fermentation.…”
Section: Resultssupporting
confidence: 90%
“…The decrease in the CP values can be possibly explained by the degradation of the protein compounds via the activity of microorganisms, which is also demonstrated by the increase in the NPN/TN contents as the water levels are increased. The values obtained in this experiment for CP are above the 8.71 and 8,9% of DM obtained for silage of corn grain with 35 and 30% of moisture at 64 and 30 days after ensiling, respectively (Morais et al, 2012;Ferraretto et al, 2018).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…For the trial with brewers' grain-based TMR, the main bacteria found in the stable silages were L. buchneri, but for the soybean curd-based TMR, the main LAB found were P. acidilactici and L. brevis [78], showing potential association of those bacteria to preserve TMR silages. A similar trial was performed by Ferraretto et al [79] to test how the process influenced luminal in vitro starch digestibility. They used dry ground corn to adjust the humidity level of wet brewers' grain and observed an increase in digestibility of the starch from the combined feed.…”
Section: Co-ensiling Forage With Food Processing Waste and Tmr Consermentioning
confidence: 99%
“…Silage is a common processing method of high-moisture feed; however, most sugars are removed from WBG during the malting process leaving inadequate levels of the substrate (water-soluble carbohydrates, WSCs) for silage fermentation, which can result in silage failure [ 5 ]. Adding a substrate to WBG to enhance its DM and WSC concentrations is an option that can improve the fermentation effect of WBG.…”
Section: Introductionmentioning
confidence: 99%